Cardiovascular risk in 18-60-years-old population in Tunja, Colombia - Vargas, Clara Elizabeth; Ortega, Sindy Juliana; Leandro, Katerin; Alfonso, Margaret Lorena; Sandoval, Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Coronary and / or cardiovascular risk is the probability that an individual develops coronary or cardiovascular disease in a specific period of time with high rates of morbidity and mortality in any stage of life. The current study aims to determine the cardiovascular risk in individuals 18 to 60 years old in the city of Tunja, Colombia, through a descriptive cross-sectional study with a qualitative approach. The sample studied was 456 people with a reliability of 95% and a margin of error of 5%, a non-probabilistic convenience sampling by quotas was taken into account. The results established for the studied population a cardiovascular risk of 22.4% (95% CI 18-25) as well as statistically significant associations between risk and sedentary variables (X2 4.87, p = 0.027) and index body mass (108.28 X2 p = 0.000). The research project allows concluding that there is a high frequency of sedentary lifestyle, low cardiovascular risk with greater frequency in women and an association between cardiovascular risk and body mass index in a group of individuals who were studied.